Intellectual life : its spirit, conditions, methods - Sertillanges,A.G. (Ireland The Catholic University of America Press, 1987)
Fr. Sertillanges's teachings are as timeless as any truths which describe the genuine nature of things.
Keywords: Inspiration--Religious aspects; Intellectual life